Navigating Islamic Da'wah for Polygamous Family Resilience: Family Communication and the Islamic Mindset - Rubani, Mardhiah; Sazali, Hasan; Metia, Cut (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research examines navigating polygamous family dynamics: family communication and mindset in an Islamic context using a mixed methods explanatory model. Quantitative data from respondents to measure the correlation and influence of family communication, family structure, and religious orientation on the resilience of polygamous families. In contrast, qualitative data from informants were used to analyze navigating polygamous family dynamics: family communication and mindset in an Islamic context which includes communication in building family meaning, relationship maintenance, and problem-solving in polygamous families. The results showed that the resilience of polygamous families can be maintained if family communication, family structure, and religious orientation used are in line with or well accepted by all family members. The calculated F value of 51.331> the F table value of 2.73 and the sig value is 0.01 <0.05 then H0 is rejected and Ha is accepted, meaning that the variables of Family Communication (X1), Family structure (X2), and Religious orientation (X3) affect family resilience (Y). Islamic Da'wah, when applied correctly and contextually, can play an important role in strengthening the resilience of polygamous families by improving effective communication and using the right Islamic mindset.